Environmental implications and spatial distribution of natural radionuclides and heavy metals in sediments from four harbours in the Egyptian Red Sea coast. (January 2018) - El-Taher, Atef; Zakaly, Hesham M.H.; Elsaman, Reda
Abstract: Measurements of natural radionuclides concentrations ( 226 Ra, 232 Th and 40 K) in sediments collected from sea, rivers or ocean is significant to protect the sea water ecosystem and to human health from radiation. Thirty-three sample of sediment have been collected from four ports in the Red Sea coast, Egypt for investigation by gamma-ray spectrometer using NaI(Tl) detector. The average and range activity concentrations of 226 Ra, 232 Th and 40 K were 26(5–58), 19(4–33) and 458(16–2665) Bq kg −1 in Quseir Harbour, 30(14–53), 20(14–34) and 430(378–511) Bq kg −1 in Abu-Tartour Harbour. However, the average and range activity concentrations were 23(14–35), 21(15–32), and 602(327–821) Bq kg −1 in Touristic Harbour and 14(5–26), 13(2–23) and 489(36–950) Bq kg −1 in Hurghada harbour. These results were compared with reported ranges in the literature from other location in the world. The radiation hazard parameters; radium equivalent activity annual dose, external hazard were also calculated and compared with the recommended levels by UNSCEAR reports. Eight heavy metals (Fe, Mn, Ni, Co, Zn, Cu, Pb and Cd) have been measured and analyzed by atomic absorption spectrometer. The concentration for the investigated heavy metals overtakes the allowable limits recommended by the Canadian Environmental Quality Guidelines. Because there are no existing databases for the natural radioactivity in the sediment samples from Egyptian Red Sea ports, our results are a start to establishing a database for Red Sea harbours environment. Highlights: Sediment samples from four ports in the Red Sea coast, Egypt were collected for investigation. The radiation hazard parameters; were also calculated and compared with the recommended reports. Eight heavy metals (Fe, Mn, Ni, Co, Zn, Cu, Pb and Cd) have been measured and analyzed by AAS.